PENGARUH PAJAK, TUNNELING INCENTIVE, PROFITABILITY DAN DEBT COVENANT TERHADAP TRANSFER PRICING (PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Mas Bayu Anggah, Wahyu; Yuliati, Anik (UMSurabaya Publishing, 2024)
This study aims to examine the influence of Tax, Tunneling Incentive, Profitability and Debt Covenant on Transfer Pricing in the Manufacturing Companies in the Food and Beverage Sub-Sector listed on the Indonesia Stock Exchange for the period 2018 – 2022. This research is descriptive research with a quantitative approach. The research sample was taken using a purposive sampling technique with the acquisition of 17 companies. The data was analyzed and tested using Statistical Product and Service Solution (SPSS) Version 26. The results of this research show that Tax is able to contribute to Transfer Pricing, Tunneling Incentive is able to contribute to Transfer Pricing. Meanwhile Profitability has not been able to contribute to Transfer Pricing. Similarly, Debt Covenant has not been able to contribute to Transfer Pricing.